Kinematic Test in Multimedia Formats: A Preliminary Validation - Sentot Kusairi (UIKTEN, 2021)
In physics, computer-based tests have been widely developed, however, the questions are only presented in textual and pictorial representations. We have developed a kinematic test in the multimedia format, which is so called multimedia-based test (MBT). For comparative study purposes, two groups of students were alternately set to take the MBT and paper-based test (PBT). From the statistical analysis, it is revealed that there was no significant difference between the MBT and PBT. Therefore, the MBT can be used for reliable assessment tool. We also found that students were more motivated to work on multimedia format.